THE PESANTREN DAY MODEL AS AN INNOVATION IN STRENGTHENING MEMORIZATION AND VALUES OF PESANTREN IN MADRASAH - Putri Avnita Mahfudzoh; Himmatul Fitria (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2026)
The development of Islamic education in the modern era requires innovative learning models that integrate Islamic values with relevant and meaningful approaches for students. One such innovation is the implementation of the pesantren day program at MI Darul Ulum Medali as a pesantren-based learning model using a non-boarding system. This study aims to examine the implementation, effectiveness, and character values developed through the pesantren day program in strengthening Qur’anic memorization and student character formation. This research employed a qualitative case study approach, with data collected through observation, in-depth interviews, and documentation involving the principal, supervising teachers, and students. The findings indicate that the pesantren day program has been systematically implemented since the odd semester of 2025 using the 5T framework, consisting of Taabbud, Talaqqi, Tahsin, Tahfidz, and Tajwid. The program was found to be effective in improving students’ fluency and accuracy in Qur’anic memorization, increasing their confidence in reciting memorization, and enhancing active participation in religious activities. Furthermore, the program contributed to positive character development, including discipline, independence, responsibility, politeness, and religiosity through continuous religious habituation and intensive teacher guidance. Therefore, the pesantren day program serves as a relevant and effective educational innovation in Islamic primary education by integrating Qur’anic memorization strengthening and character education in a holistic and sustainable manner.